Useful Ideas when Taking Songs to a Class - Lopera, Sergio (Íkala, Revista de Lenguaje y Cultura, 2003)
This article gives some basic ideas when teaching English with songs. Also some reasons why EFL teachers take songs are given. It addresses two important issues when teaching with songs: selection of songs and preparation of tasks. Examples for each kind of task are given. This paper recommends a routine of designing tasks that follow the format of pre-activities, while-listening activities and post-activities. Received: 29-05-03 / Accepted: 18-09-03. How to reference thus article: Lopera, S. (2003). Useful Ideas when Taking Songs to a Class. Íkala. 8(1), pp. 135 – 149